Small-diameter vascular graft using co-electrospun composite PCL/PU nanofibers. (6th August 2018) - Jirofti, Nafiseh; Mohebbi-Kalhori, Davod; Samimi, Abdolreza; Hadjizadeh, Afra; Kazemzadeh, Gholam Hossein
Abstract: Small-diameter vascular scaffolds have been developed by a co-electrospinning method using polyethylene terephthalate (PCL) and elastic polytetrafluoroethylene (PU) as biopolymers with long degradation time. Although they possess favorable properties, individually these two polymers do not meet the requirements for the production of synthetic vascular scaffolds. The co-electrospinning method was adopted to develop and mechanically improve the composite PCL/PU vascular scaffolds. The morphological, mechanical and biological properties of these vascular scaffolds were evaluated through scanning electron microscopy, differential scanning calorimetry, Fourier transform infrared spectroscopy, compliance, tensile testing and MTT assay. The in vivo study of the vascular scaffolds was performed by implanting them on rat and sheep models. The compliance of the composite vascular scaffolds improved by up to 43% through an increased percentage of PU from 10%–90%. The obtained UTS of the scaffolds at 10%, 25%, 50%, 75% and 90% of PU were 4.7 ± 0.34, 3.4 ± 0.6, 4.8 ± 0.62, 2.2 ± 0.34 and 4.4 ± 1.9 MPa, respectively. The results of MTT assays indicated that the cell growth on the scaffolds was augmented when compared to the control, from day one to day seven. Mild edema, mild foreign-body granulomatous reaction and mild fibrosis were observed by pathology test as the side effects in the composite scaffold with 50% PCL. Doppler ultrasound and angiography images confirm that no aneurysm, thrombogenesis, neointimal hyperplasia or occlusion exist, and there is complete patency at the end of an eight month investigation. The fabricated composite vascular scaffolds provide appropriate mechanical and biological properties and clinical requirements, indicating their required potential to be applied as a small-diameter vascular graft.